A ratiometric fluorescent sensor made of a terbium coordination polymer for the anthrax biomarker 2, 6-dipicolinic acid with on-site detection assisted by a smartphone app. Issue 1 (24th November 2021) - Qiu, Miao-Miao; Chen, Ke-Fu; Liu, Qi-Rui; Miao, Wei-Ni; Liu, Bing; Xu, Ling
Abstract : Tb-NDBC is a quantitative ratiometric fluorescence sensor for DPA detection with high sensitivity and selectivity, a rapid response, and durability. Abstract : A ratiometric fluorescence sensor consisting of [Tb(NDBC)(COO)] (Tb-NDBC) shows high sensitivity and selectivity during DPA detection in natural lake water and human serum samples. A self-programmed smartphone app can calculate the DPA concentration by reading green values, realizing on-site DPA detection.